Bess W. Truman - Truman, Margaret, 1924- (New York : Macmillan, 1986)
Describes the life of Bess Truman, her marriage, and her influence on her husband's career as seen through the eyes of her daughter and through personal correspondence
Includes index.
Keywords: Truman, Bess Wallace; Truman, Harry S., -- 1884-1972 -- Family; Presidents$1 (Bspousess -- United States -- Biography; Presidents -- United States -- Biography